Trans Women and Public Restrooms: The Legal Discourse and Its Violence - Bagagli, Beatriz Pagliarini; Chaves, Tyara Veriato; Zoppi Fontana, Mónica G. (Frontiers in Sociology, 2021)
Safe access to public restrooms is an essential need for participation in civic life, in the workplace, in educational settings and other public spaces. This is no different for transgender people. However, access to public restrooms according to gender identity has sparked controversy to the extent that transgender people face embarrassment and even expulsion from these spaces. The lack of access of the transgender population to public restrooms has a negative impact on the physical and mental health of this population. Thus, this article aims to address the main consequences that the ban on the use of bathrooms has for the transgender population, specifically the access of transgender women to the women’s restroom. We covered some legal aspects of “bathroom laws” and the main arguments in this discussion. We understand that the prohibition of access to the restroom constitutes a form of gender violence and discrimination, as we conclude that the arguments that express concerns about safety are not supported.